A review on optimizing fish growth using fermented animal by-products for sustainable aquaculture - Hasna Nabila Shobihah; Yuli Andriani; Muhamad Fatah Wiyatna; Iskandar Iskandar; Irfan Zidni; Mia Miranti Rustama (Depik Jurnal)
Feed availability is a crucial factor in aquaculture, accounting for approximately 60–70% of total production costs. High-quality feed is often expensive due to reliance on imported ingredients. To address this issue, animal-based organic waste presents a promising alternative, given its abundance, underutilization, and high nutritional value when properly processed. This review was conducted from November 2024 to January 2025 using a narrative literature review approach, synthesizing previous publications to identify research gaps and development opportunities. Literature was sourced from national and international scientific databases, including Scopus, ScienceDirect, SpringerLink, and ResearchGate. The study aimed to explore the production of fermented animal by-product meal and its application in aquafeed to enhance fish growth performance. Findings indicate that fermentation significantly improves the nutritional quality of animal waste. Several reviewed studies reported that incorporating fermented by-products such as fish offal, poultry feathers, and blood at inclusion levels of 20–25% can improve the growth and survival rates of juvenile fish. Therefore, the optimal use of such ingredients is recommended to reduce feed costs and support the sustainability of aquaculture systems.